2021
DOI: 10.1111/acps.13349
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain abnormalities associated with cognitive impairments in bipolar disorder

Abstract: Objective Cognitive impairment has been highlighted as a core feature of bipolar disorder (BD) that often persists during remission. The specific brain correlates of cognitive impairment in BD remain unclear which impedes efficient therapeutic approaches. In a large sample of remitted BD patients, we investigated whether morphological brain abnormalities within dorsal prefrontal cortex (PFC) and hippocampus were related to cognitive deficits. Methods Remitted BD patients (n = 153) and healthy controls (n = 52)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
0
7
0
1
Order By: Relevance
“…O comprometimento cognitivo vem sendo estudado em pacientes com TB como uma das principais características. O estudo de Macoveanu (2021), testou uma amostra de pacientes em remissão da doença para investigar as anormalidades morfológicas cerebrais no hipocampo e no córtex pré-frontal dorsal, e se as mesmas estão relacionadas a déficits cognitivos.…”
Section: Resultsunclassified
“…O comprometimento cognitivo vem sendo estudado em pacientes com TB como uma das principais características. O estudo de Macoveanu (2021), testou uma amostra de pacientes em remissão da doença para investigar as anormalidades morfológicas cerebrais no hipocampo e no córtex pré-frontal dorsal, e se as mesmas estão relacionadas a déficits cognitivos.…”
Section: Resultsunclassified
“…These rsFC abnormalities may arise from disruption of structural connectivity due to white matter deficits that have been observed in CI relative to CN patients with mood disorders and HC. 52,53 Interestingly, an MRI study exploring the corpus callosum (CC) in children and adolescents with BD found a lower circularity of the splenium of the CC in a sample of pediatric patients with BD relative to HC, suggesting that such white matter abnormalities may occur early in the course of BD. 54 Indeed, this lends support to the hypothesis of an abnormal neurodevelopmental trajectory in BD.…”
Section: Discussionmentioning
confidence: 99%
“…Second, from a theoretical perspective, it is interesting that rsFC abnormalities were seen both within and between DMN and ECN in partially overlapping parietal and PCC areas. These rsFC abnormalities may arise from disruption of structural connectivity due to white matter deficits that have been observed in CI relative to CN patients with mood disorders and HC 52,53 . Interestingly, an MRI study exploring the corpus callosum (CC) in children and adolescents with BD found a lower circularity of the splenium of the CC in a sample of pediatric patients with BD relative to HC, suggesting that such white matter abnormalities may occur early in the course of BD 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this, recent fMRI studies that compared neuronal activity between cognitively impaired (with global cognition scores ≥1 SD below the mean of healthy controls) and cognitively normal people with BD found that cognitive impairments were associated with working memory(WM)‐related hypo ‐activity in the DPFC and parietal regions coupled with hyper ‐activity in the DMN 12,13 . At a structural level, cognitively impaired BD individuals were found to display lower cerebral white matter volume and greater DPFC volume or grey matter, respectively, than cognitively normal individuals and healthy participants 14,15 . In MDD, extensive white matter dysfunction has also been observed in globally cognitively impaired individuals relative to those with either selective impairments or normal cognition 16 .…”
Section: Introductionmentioning
confidence: 91%
“… 12 , 13 At a structural level, cognitively impaired BD individuals were found to display lower cerebral white matter volume and greater DPFC volume or grey matter, respectively, than cognitively normal individuals and healthy participants. 14 , 15 In MDD, extensive white matter dysfunction has also been observed in globally cognitively impaired individuals relative to those with either selective impairments or normal cognition. 16 However, other structural studies in BD revealed no differences between impaired and normal neurocognitive subgroups, 12 , 17 suggesting that task‐based fMRI could be a more sensitive assay of cognitive impairments.…”
Section: Introductionmentioning
confidence: 99%